PERBEDAAN PENGARUH BACK STRENGTHENING EXERCISE DAN PILATES EXERCISE TERHADAP AKURASI TENDANGAN PADA PEMAIN SEPAK BOLA - Virka Sari, Deasy; Adiatmika, I Putu Gede; Imron, M. Ali; Tianing, Ni Wayan; Sagung Sawitri, Anak Agung; Lesmana, S. Indra (Sport and Fitness Journal; Volume 7, No.2, Mei 2019, 2019)
Background: Kick accuracy is a person's ability to control free movements against a target. Kick accuracy are influenced by core muscles, concentration and dynamic balance. Back strengthening exercise and Pilates exercise was given by the researcher to improve the accuracy of kicking among soccer players. Purpose: The difference effect of back strengthening exercise and Pilates exercise on kick accuracy among soccer players. Methods: This study was quasi-experimental with a pre-test and post-test group design. There were 22 subjects divided randomly into 2 groups. Group I with back strengthening exercise and group II Pilates exercise. Exercise was given 3 times a week for 5 weeks. Kick accuracy measurement tool used plywood target measurement. Result: research shows that the intervention that was given to groups I and II could improve kick accuracy in soccer players. The effect test are using paired sample t-test in group I with mean pre and post test, obtained (p=0.004) and in group II obtained (p=0.011). The different test among two groups are using independent sample t test with post treatment data in each group, obtained (p=0.100). Conclusion: There is no difference in the effect between giving back strengthening exercise and Pilates exercise to the accuracy of kick on the soccer player.